Educational supervision and its relationship with teaching performance in educational institutions of the network No. 08 Puente Piedra - Lima- 2014 - Martínez Salomón, Niséfora (2019)
The research we have done is basic causal correlational experimental study factors are two educational supervision and teacher performance. The population sample consisted of 34 teachers and hierarchical RED Pedra Bridge 08. The research design is transactional, correlational, causal, bivariate cross.                                      For data collection two structured questionnaires were prepared, the instruments meet the qualities of validity and reliability. The study raises the following research hypothesis: There is significant relationship between educational supervision and teacher performance in the educational institutions of the Red N ° 08 - Stone Bridge-Lima - 2014. The results allow us to reject the null hypothesis and accept the hypothesis investigated by applying the formula of Spearman Rho with a significance level of 95% found that the correlation coefficient Spearman Rho is 0.903 and the value is 0.000 p_ by thus we establish that correlation has a very good level, we see that there is a direct and a significance level of less than 0.05 for that reason we reject the null hypothesis and accept the alternative.